The Impact of Artificial Intelligence on Recruitment and Talent Acquisition: Challenges and Opportunities - Radha, P; Swathi, P; Subbulakshmi, P E; Mirsath Begum, M (SAIM Journal of Social Science and Technology, 2025)
Purpose: This study investigates the transformative impact of Artificial Intelligence (AI) on recruitment and talent acquisition, focusing on AI’s potential to enhance efficiency, reduce bias, and improve candidate experiences, while also addressing associated ethical, privacy, and technological challenges. Design/Methodology/Approach: The research employs a comprehensive review of existing literature and case studies to explore the opportunities and challenges presented by AI-driven recruitment processes . Findings: The analysis reveals that AI substantially improves recruitment efficiency and bias mitigation, contributing to more positive candidate experiences. However, it also highlights critical concerns related to ethical implications, data privacy, and the dangers of over-reliance on AI without adequate human oversight. Implications: These insights guide HR professionals and organizations in optimizing recruitment practices in an AI-driven environment. Originality: this research offers a nuanced perspective on AI integration in recruitment, emphasizing the interplay between technological innovation and ethical considerations—a timely contribution to HR technology scholarship.